Non-invasive quantification of stem cell-derived islet graft size and composition - Lithovius, Väinö; Lahdenpohja, Salla; Ibrahim, Hazem; Saarimäki-Vire, Jonna; Uusitalo, Lotta; Montaser, Hossam; Mikkola, Kirsi; Yim, Cheng-Bin; Keller, Thomas; Rajander, Johan; Balboa, Diego; Barsby, Tom; et al. (Springer Nature, 2025)
Aims/hypothesis: Stem cell-derived islets (SC-islets) are being used as cell replacement therapy for insulin-dependent diabetes. Non-invasive long-term monitoring methods for SC-islet grafts, which are needed to detect misguided differentiation in vivo and to optimise their therapeutic effectiveness, are lacking. Positron emission tomography (PET) has been used to monitor transplanted primary islets. We therefore aimed to apply PET as a non-invasive monitoring method for SC-islet grafts.
Methods: We implanted different doses of human SC-islets, SC-islets derived using an older protocol or a state-of-the-art protocol and SC-islets genetically rendered hyper- or hypoactive into mouse calf muscle to yield different kinds of grafts. We followed the grafts with PET using two tracers, glucagon-like peptide 1 receptor-binding [18F]F-dibenzocyclooctyne-exendin-4 ([18F]exendin) and the dopamine precursor 6-[18F]fluoro-L-3,4-dihydroxyphenylalanine ([18F]FDOPA), for 5 months, followed by histological assessment of graft size and composition. Additionally, we implanted a kidney subcapsular cohort with different SC-islet doses to assess the connection between C-peptide and stem cell-derived beta cell (SC-beta cell) mass.
Results: Small but pure and large but impure grafts were derived from SC-islets. PET imaging allowed detection of SC-islet grafts even <1 mm3 in size, [18F]exendin having a better detection rate than [18F]FDOPA (69% vs 44%, <1 mm3; 96% vs 85%, >1 mm3). Graft volume quantified with [18F]exendin (r2=0.91) and [18F]FDOPA (r2=0.86) strongly correlated with actual graft volume. [18F]exendin PET delineated large cystic structures and its uptake correlated with graft SC-beta cell proportion (r2=0.68). The performance of neither tracer was affected by SC-islet graft hyper- or hypoactivity. C-peptide measurements under fasted or glucose-stimulated conditions did not correlate with SC-islet graft volume or SC-beta cell mass, with C-peptide under hypoglycaemia having a weak correlation with SC-beta cell mass (r2=0.52).
Conclusions/interpretation: [18F]exendin and [18F]FDOPA PET enable non-invasive assessment of SC-islet graft size and aspects of graft composition. These methods could be leveraged for optimising SC-islet cell replacement therapy in diabetes.